Systems neuroscience: a box full of tools to illuminate the black box of the brain - Wiegert, Simon; Spehr, Marc; Hanganu-Opatz, Ileana (PLoS biology, 2023)
Investigation of brain function has been fueled by an accelerating development of novel technologies and tools. This Perspective looks at the unprecedented neurotechnological progress of the past 2 decades and discusses future strategies to elucidate brain function.
Veröffentlicht: 27. Juli 2023
Gesehen am 02.10.2023